Child-Proofing Your Yard - Patricia Bartlett; Suzanna Smith (EDIS, 2012)
“Once your child first pulls himself or herself onto two feet, normal housekeeping rules fly out the window as every parent makes child-proofing a high priority. These precautions become even more elaborate as the child becomes more mobile and more creative. But experts at the University of Florida point out that a backyard poses just as many hazards—but hazards of a different sort than a home.” This 2-page Family Album Radio transcript was written by Patricia Bartlett and Suzanna Smith, and published by the UF Department of Family, Youth and Community Sciences, September 2012.